1996
DOI: 10.2307/3579392
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Salivary Gland Tumors among Atomic Bomb Survivors, 1950-1987. Evaluation of Radiation-Related Risk

Abstract: A wide-ranging search for benign and malignant tumors of the major and minor salivary glands among members of the Life Span Study sample of the Radiation Effects Research Foundation identified 41 malignant and 94 benign incident tumors, including 14 malignant and 12 benign tumors of the minor salivary gland, plus 10 major gland tumors of unknown behavior. Dose-response analyses found statistically significant increases in risk with increasing A-bomb dose for both cancer and benign tumors. Estimated relative ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 25 publications
5
44
1
3
Order By: Relevance
“…In the present study, however, we found p53 mutational points in Warthin tumor cases which were highly shared among the sample group, although those point mutations did not affect the amino acid translation so much, indicating that they were just genetic polymorphisms. As shown in the sequencing (14,42). The present data indicate a possibility that immunological or inflammatory stimuli tend to be associated with some intrinsic background such as p53 gene polymorphisms in the pathogenesis of Warthin tumor.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In the present study, however, we found p53 mutational points in Warthin tumor cases which were highly shared among the sample group, although those point mutations did not affect the amino acid translation so much, indicating that they were just genetic polymorphisms. As shown in the sequencing (14,42). The present data indicate a possibility that immunological or inflammatory stimuli tend to be associated with some intrinsic background such as p53 gene polymorphisms in the pathogenesis of Warthin tumor.…”
Section: Discussionsupporting
confidence: 59%
“…Together with Warthin tumors, mucoepidermoid carcinomas have been shown to be related to radiation in their pathogenesis (14)(15). Therefore, these two tumors were simply expected to share certain common gene mutational backgrounds caused by radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radno okruženje u drvnoj industriji i industriji prerade guma kao i prisustvo silikonske prašine dovodi se u vezu sa nastankom malignih tumora pljuvačnih žlezda [5]. Postoje indicije da izlaganje ultraljubičastoj [24] ili jonizujućoj radijaciji [25,26] može povećati rizik od nastanka karcinoma pljuvačnih žlezdi. Kumulativno izlaganje opisanim faktorima može objasniti učestalost ovih karcinoma u kasnijem životnom dobu.…”
Section: Diskusijaunclassified
“…Other rare mucoepidermoid cancer^like tumors that can arise from several different organ sites have not yet been tested for the presence of the fusion oncogene. B, mapping of the t(11;19) chromosomal breakpoint, which occurs within intron 1of both the Mect1/Torc1 and Maml2 genes in all cases tested and which results in exon 1 swapping between the genes.Whereas the etiologic events leading to the t(11;19) are unknown in most cases, mucoepidermoid cancer presents commonly as a secondary cancer in children and shows an exceptionally strong radiation dose response risk (30,31 Taken together, these reports allow us to make several predictions and speculations. First, we can now recognize that high-grade or poorly differentiated mucoepidermoid cancer is a distinct genetic entity from low-grade malignancies.…”
mentioning
confidence: 99%